Examining Disability, Pain, and Anxiety in Patients Following Lumbar Decompression Surgery: A Cross-Sectional Study - Abdus Samad Khan; Muhammad Bilal; Naeem Ul Haq; Aiman Zia; Haziq Dad (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Lumbar decompression surgery is commonly performed to alleviate symptoms of lumbar spine diseases; nevertheless, the correlation between post-operative impairment and factors such as pain severity, pain-related anxiety, and physical performance remains little studied. This study aimed to investigate these relationships in patients following lumbar decompression surgery.